Well-being and well-becoming through the life-course in public health economics research and policy: A new infographic - Edwards, Rhiannon Tudor (Frontiers in Public Health, 2022)
Background: The term “well-becoming” is not new, but is not routinely used in our everyday language or in research in public health economics. It has been applied in early years research. Objective: To develop a new infographic in the spirit of the Dahlgren and Whitehead (2006) rainbow infographic of social determinants of health. The purpose being to redefine well-being as a process of growth through life, articulated as well-becoming. Methods: A rapid review of life-course stage appropriate models of well-being with stages of the life-course as defined as: preconception and birth; early years; adolescence; working, parenting and caring; older age, and death. Results: A new infographic reflecting an underlying concept of “the wheel of life”. It shows movement through the life-course at its centre, with concentric rings summarising personal, local, and national and global factors that have an impact on well-being and well-becoming of individuals through the life-course. Prepared during 2021-22, the infographic reflects the role of pandemic and war within the national and global ring of influential factors. I reflect on three ways in which health economists are currently using a life-course approach and the concept of well-becoming in the economic evaluation of individual programs and at a population level of government policy. Conclusion: Moving from solely focusing on a concept of well-being to a concept of well-being and well-becoming acknowledges the influence that socioeconomic and other conditions in a particular life-course stage have on subsequent life-course stages, and the cost-effectiveness of intervening across the life-course.